Analisis Praktik Manajemen Kualitas, Strategi Bisnis dan Pelaporan Kinerja pada Perusahaan Bersertifikat ISO 9000 dan Perusahaan Non-ISO 9000 - Anas Wibawa (The Indonesian Journal of Accounting Research, 2013)
ISO 9000 certification is a recent phenomenon. An increasing number of organizations are obtaining ISO accreditation from the International Organization for Standardization (ISO). ISO 9000 series (Quality Management and Quality Assurance Standard) outlines the requirement to be met by producers ilustrating their competence to design, produce and deliver products and services with a consistence level of quality. Although ISO accreditation may reflect an organization’s pursuit of a quality focused, business strategy and commitment to management quality practices, ISO acreditation may merely be a response to external demand for quality certification. This reseach examines whether ISO accredited companies differ from non ISO accredited companies in quality management practices, business strategy, and quality performance measurement.Based on mail questionaire sent to a sample of ISO accredited and non ISO accredited in Indonesia manufacturing companies, the results showed a significant difference in quality management practices for small entreprizes with and without ISO certivication? However, there was no significant differences in the business strategy and quality performance measurement between ISO accredited companies and non ISO accredited companies.